Phytogenic blend in the diet of growing Holstein steers: Effects on performance, digestibility, rumen volatile fatty acid profile, and immune and antioxidant responses - Brunetto A.L.R.* (2023)
© 2023 Elsevier B.V.The present study determined whether adding the phytogenic blend to the diet of growing steers would improve weight gain, the apparent digestibility of nutrients, volatile fatty acid profiles, and alter immune and antioxidant responses. The experiment included 24 Holstein calves, with an average weight of 149.6 ± 5 kg maintained in a semi-confinement system. The animals were divided into two groups (treated and control). In the concentrate of the treated group, the test product was a phytogenic blend composed of micro-encapsulated cinnamon and oregano essential oils, free turmeric extract, and tannic acid. The animals in the treated group showed more significant weight gain than the control on day 30; there was a trend toward more significant weight gain from 1 to 60 days (P = 0.07). Butyric acid concentrations were higher in the rumen, and there was an interaction between treatment and day (day 30) in the treated group. The ruminal acetic and propionic acid concentrations were higher in animals in the treated group on day 30. The intake of the phytogenic blend increased the apparent digestibility coefficient of neutral detergent fiber but did not affect the apparent digestibility coefficient of dry matter, crude protein, or mineral matter. There were significantly fewer lymphocytes in the treated group on day 30. There was a treatment effect and interaction between treatment and day for cholesterol levels, with lower levels in the treated group than in the control group. Serum glucose concentrations were lower in animals in the treated group. There was an effect of the treatment on the concentration of total proteins and globulins, with the highest levels of these proteins in the animals in the treated group. Protein electrophoresis revealed that IgA and ceruloplasmin levels showed a treatment effect and interaction, with higher levels in the treated group (P < 0.05). Heavy chain immunoglobulin levels were lower in steers in the treated group at day 90. Thiobarbituric acid reactive substance levels were lower in the treated group, indicating less lipid peroxidation (P < 0.05). We found that the levels of reactive oxygen species were lower in the treatment group at day 30, and glutathione S-transferase activity and protein thiol levels were higher in this group. These findings suggest that adding the phytogenic blend to the animals' diet was critical in the initial phase, as it modulates volatile fatty acids, stimulates immunological biomarkers, and has antioxidant activity.